PERLINDUNGAN HUKUM TERHADAP PERJANJIAN PERKAWINAN DALAM HARTA PERKAWINAN - Normala Sari (2023)
This study aims to analyze the legal protection of assets in marriage after the deed of marriage agreement is made and its impact, in relation to the unclear provisions regarding the validity of marriage. The marriage contract provides objective protection to those who have more wealth. For those who are economically disadvantaged, a marriage agreement can be used as a means of legal protection by expanding the contents of the marriage agreement by including things that can happen in the marriage. Marriage is a legal act that has legal consequences. Normative-juridical methods and qualitative research were used in this study with a statute approach and a conceptual approach. This research consists of several data sources, namely primary, secondary and tertiary legal materials. This research shows that with the existence of a prenuptial agreement to protect the rights and obligations of the parties after the divorce so that no party is harmed Keywords: Legal Protection, Marriage Agreement, Marriage.